ANALISIS DEPRESIASI AKTIVA TETAP ALAT BERAT DALAM MENINGKATKAN LABA PERUSAHAAN KONTRAKTOR PERTAMBANGAN DAN PERDAGANGAN (Studi Kasus pada PT. Aneka Mineral Mining di Pomalaa) - Nurul Hidayati; Sasmita Nabila Syahrir; Surianto Ilham (Jurnal Akuntansi Kompetif, 2026)
Analysis of Fixed Asset Depreciation in Increasing the Profit of Mining and Trading Contractor Companies (Case Study of PT. Aneka Mineral Mining in Pomalaa). This research aims to conduct a comparative analysis of depreciation methods to identify the advantages and disadvantages of each, so that researchers can provide relevant input to companies with reference to the provisions of PSAK No. 216. In analyzing the phenomenon under study, this study adopts a qualitative perspective implemented through a case study design. Data was collected through a series of procedures including documentation tecniques, semi-structured interviews, and direct observation in the field. Data analysis techniques use constant comparative techniques to compare the depreciation methods currently used by companies with relevant depreciation methods. Keywords: Depreciation Method, Fixed Assets, Profit Increase.